Clays and Clay Minerals, Vol. 55, No. 2, 220–232, 2007. - Tunega, Daniel; Goodman, Bernard A.; Haberhauer, Georg; Reichenauer, Thomas G.; Gerzabek, Martin H.; Lischka, Hans (The Clay Minerals Society, 2007)
An ab initio theoretical approach has been used to calculate optimized geometries and the relative energies of various compositional arrangements in structures of dioctahedral smectites based on models consisting of two unit-cells. These calculations indicate that the energy differences between structures having vacancies in sites with cis- or trans-OH coordination are small and that their relative energies vary with the chemical nature of the substitutions. For example, a cis-OH coordination for the vacancy was the most stable when the interlayer charge originated from substitution of Al for Si in the tetrahedral sheet, whereas the trans-coordination was the more stable for most cases of substitution in the octahedral sheet, an exception being Fe(II) for Al where the cis-OH coordination was favored. It seems likely, therefore, that long-range structural disorder will be a common phenomenon in natural phyllosilicate specimens.
Ab Initio Calculations Of Relative Stabilities Of Different Structural Arrangements In Dioctahedral Phyllosilicates
Clays and Clay Minerals, Vol. 55, No. 2, 220–232, 2007. Ab Initio Calculations Of Relative Stabilities Of Different Structural Arrangements In Dioctahedral Phyllosilicates. Daniel Tunega; Bernard A. Goodman; Georg Haberhauer; Thomas G. Reichenauer; Martin H. Gerzabek; Hans Lischka. DOI: 10.1346/CCMN.2007.0550211. Copyright © 2007, The Clay Minerals Society.
Keywords: Periodicals; Geology; Ab Initio; Dioctahedral; Phyllosilicates; Smectite; Cis- and Trans-coordination